2020
DOI: 10.1136/bmjspcare-2020-002195
|View full text |Cite
|
Sign up to set email alerts
|

Palliative versus hospice care in patients with cancer: a systematic review

Abstract: BackgroundGuidelines recommend an early access to specialised palliative medicine services for patients with cancer, but studies have reported a continued underuse. Palliative care facilities deliver early care, alongside antineoplastic treatments, whereas hospice care structures intervene lately, when cancer-modifying treatments stop.AimThis review identified factors associated with early and late interventions of specialised services, by considering the type of structures studied (palliative vs hospice care)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 93 publications
2
12
0
Order By: Relevance
“…Hospice services: community-based care that is offered, ideally, by a multidisciplinary team that supports patients with advanced disease and their families, [ 28 ] and can be provided in a patient’s home setting or in palliative and hospice facilities. Hospice care may be provided to outpatients or inpatients [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hospice services: community-based care that is offered, ideally, by a multidisciplinary team that supports patients with advanced disease and their families, [ 28 ] and can be provided in a patient’s home setting or in palliative and hospice facilities. Hospice care may be provided to outpatients or inpatients [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the growth of health care, hospice care has become a popular area of humanistic medical care. Hospice care is a type of medical care that focuses on alleviating the symptoms of a patient’s illness and slowing its progression in the weeks or even months before their death [ 43 ]. Research has shown that medical students can develop personal reflection and empathy skills as hospice volunteers [ 44 ].…”
Section: The Role Of Medical Students’ Participation In Volunteer Ser...mentioning
confidence: 99%
“…Governmental programs have regularly supported the development of inpatient palliative care (IPC) (8,9). However, data regarding the efficiency of IPC delivery among cancer patients in Europe are limited (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of studies have reported a low number of referrals for palliative care in older cancer patients (13,14). The majority of studies have analysed global cancer populations (10) and failed to compare patients with similar cancer-related needs. The comparison of IPC delivery in young and older patients with similar cancers is essential for MBC patients due to the variable prognosis of the different tumoural subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation